The emerging role of brain neuroinflammatory responses in Alzheimer’s disease - Amelimojarad, Mandana; Amelimojarad, Melika; Cui, Xiaonan (Frontiers in Aging Neuroscience, 2024)
As the most common cause of dementia, Alzheimer’s disease (AD) is characterized by neurodegeneration and synaptic loss with an increasing prevalence in the elderly. Increased inflammatory responses triggers brain cells to produce pro-inflammatory cytokines and accelerates the Aβ accumulation, tau protein hyper-phosphorylation leading to neurodegeneration. Therefore, in this paper, we discuss the current understanding of how inflammation affects brain activity to induce AD pathology, the inflammatory biomarkers and possible therapies that combat inflammation for AD.